Development of a selective hydrogen leak sensor based on chemically doped SnO2 for automotive applications. (13th April 2017) - Lavanya, N.; Sekar, C.; Fazio, E.; Neri, F.; Leonardi, S.G.; Neri, G.
Abstract: The development of a selective hydrogen leak conductometric sensor for automotive applications based on transition metal ion (Mn, Co) doped SnO2 nanoparticles is presented. Co and Mn-SnO2 nanoparticles were synthesized by microwave irradiation method. XRD, Raman, XPS and TEM studies confirmed that the dopants enter into the tetragonal rutile-type structure of SnO2 . As a result, the average crystallite sizes of the doped samples decrease with the increase in dopant concentrations. Sensors performances have been assessed by studying the signal response to hydrogen (H2 ) at different temperatures and concentrations. The selectivity of the fabricated sensors against the potential interfering gas carbon monoxide (CO) was also investigated. Results demonstrate that Co is more effective in enhancing the sensing performance of SnO2 NPs when compared to pristine and Mn-doped SnO2, allowing the fabrication of a hydrogen leak sensor with excellent response, good selectivity and reproducibility at the operating temperature of 250 °C. Highlights: A selective sensor for monitoring hydrogen leak in closed ambient was fabricated. Sensing materials composition and preparation was optimized. Good sensor performances were obtained with a Co-doped SnO2 based sensor.